Catastrophizing and Depressive Symptoms as Prospective Predictors of Outcomes Following Total Knee Replacement - Robert R Edwards; Jennifer A Haythornthwaite; Michael T Smith; Brendan Klick; Jeffrey N Katz (Pain Research and Management)
Several recent reports suggest that pain-related catastrophizing is a risk factor for poor acute pain outcomes following surgical interventions. However, it has been less clear whether levels of catastrophizing influence longer-term postoperative outcomes. Data were analyzed from a relatively small number (n=43) of patients who underwent total knee replacement and were followed for 12 months after their surgery. Previous research has suggested that high levels of both catastrophizing and depression are associated with elevated acute postoperative pain complaints among patients undergoing knee surgery. In this sample, catastrophizing and depression at each of the assessment points were studied as prospective predictors of pain (both global pain ratings and pain at night) at the subsequent assessment point over the course of one year. The predictive patterns differed somewhat across measures of pain reporting; depressive symptoms were unique predictors of greater global pain complaints, while catastrophizing was a specific and unique predictor of elevated nighttime pain. While surgical outcomes following total knee replacement are, on average, quite good, a significant minority of patients continue to experience long-term pain. The present findings suggest that high levels of catastrophizing and depression may promote enhanced pain levels, indicating that interventions designed to reduce catastrophizing and depressive symptoms may have the potential to further improve joint replacement outcomes.